The Effect of Digital Capability and Digital Literacy on Business Performance With Employee Innovation as a Mediating Variable at PT Pegadaian - Devinda Anggitasari; Eko Purwanto; Tri Kartika Pertiwi (Return : Study of Management, Economic and Bussines, 2023)
The purpose of this research was to determine the effect of digital capability and digital literacy on PT Pegadaian's micro employees on business performance both directly and through employee innovation. PT Pegadaian has a mission to be able to provide service excellence with a customer focus through simpler and digital business processes to be able to continue to compete with competitors so as to improve the company's business performance. One of the efforts that can be made to achieve this mission is that PT Pegadaian employees are required to have innovation and be supported by digital capability and digital literacy. The research is a quantitative research with convenience sampling method and data analysis using Smart PLS. The results of the analysis in show that digital capability & digital literacy do not have a direct role in improving business performance. Digital capability & digital literacy must take advantage of employee innovation to improve business performance.